Are weeds really an issue in Zero Tillage systems? Farmer insights from the Eastern Gangetic Plains of South Asia - Chaudhary, Anjana; Suri, Bhavya; Timsina, Pragya; Karki, Emma; Sharma, Akriti; Gartaula, Hom Nath; Brown, Brendan (International Maize and Wheat Improvement Center, 2023)
A large amount of literature has now proven that zero tillage (ZT) as a part of Conservation Agriculture-based Sustainable Intensification (CASI) practices has the potential to help smallholder farmers in the Eastern Gangetic Plains (EGP) of South Asia transition to more productive, profitable, and sustainable production systems. Despite this, changes in weed management under ZT are commonly identified as a constraint to wider adoption, based primarily on quantitative investigations. Yet the contribution of this to farmers’ evaluation and adoption behavior remain underexplored. To address this, we explore farmers’ perceptions on CASI-based herbicide weed management systems using semi-structured interviews from six locations across the EGP. This study identifies a divergence in experiences with herbicides, both geographically (with more negative reports from Sunsari and Bihar than other locations) and in terms of user typologies (where users are overwhelmingly positive, and nonusers are overwhelmingly negative). This divergence suggests that an information void exists that has the potential to contribute strongly to the negative evaluation of CASI, as well as potentially negative changes in household labor dynamics. To overcome this, promotional efforts should target education and training programs that address how to effectively spray, potentially with increased emphasis on weather forecasting use. This will ensure equitable outcomes for household members, and increased interest and use of CASI can be enabled.